Comprehensive Investigation of the Side-gate Effect on the RF Small-signal Equivalent Elements of AlGaN/GaN High-Electron-Mobility Transistor on a Silicon Substrate - Alghamdi, Sami (Journal of King Abdulaziz University: Engineering Sciences, 2023)
The side-gate effect on the radio frequency (RF) small-signal equivalent elements of an AlGaN/GaN HEMT on a high-resistivity silicon substrate was comprehensively studied. The side-gate bias was found to have a significant impact on the direct-current (DC) and small-signal performance of the device through the buffer layer. Gate and drain bias dependent small-signal equivalent circuit parameters were extracted at different side-gate biases, and the physical mechanism was investigated and analyzed. These findings suggest that the side-gate effects should be taken into account when monolithic microwave integrated circuits are designed based on GaN-on-Si HEMTs.